A modified technique for Gore Excluder limb deployment in difficult iliac anatomy during endovascular abdominal aortic aneurysm repair. (February 2015) - Vourliotakis, George; Katsargyris, Αthanasios; Tielliu, Ignace FJ; Zeebregts, Clark J; Verhoeven, Eric LG
Complex iliac anatomy including extreme tortuosity constitutes a relative contraindication for endovascular abdominal aortic aneurysm repair with additional risk of limb-graft occlusion. The Gore Excluder limb-graft is a flexible stent-graft, which adapts easily to iliac tortuosity. Nevertheless, the presence of the stiff guide wire does not always allow for an ideal apposition of the stent graft to the angulated common iliac artery vessel wall. We describe herein a modified technique for Gore Excluder limb-graft deployment with partial removal of the stiff wire in cases with difficult tortuous or narrow iliac arteries during endovascular abdominal aortic aneurysm repair.